Design of a 100 KW Kaplan Turbin A Case Study on a Small-Scale Hydropower System - Saidiman, Mohamad; Dewi, Rimba Krisnha; Supriyono, Toto (Sainteks: Jurnal Sain dan Teknik, 2025)
Some parts of the world, such as Indonesia, are blessed with nature that has abundant water energy potential. Water energy includes water turbines. This paper discusses planning a Kaplan-type water turbine with a capacity of 100 kW. The flow of water through Kaplan's turbines is axial. Water currents theoretically have an effective bulk height called head height, H is at least 5 (five) meters with a minimum theoretical discharge of 4.25 m3/s. The results of the calculation show that this Kaplan-type water turbine can produce maximum power at a theoretical discharge of 166.77 kW. The velocity of water entering the turbine inlet chamber is 3.123 m/s, while the theoretical velocity is 13.48 m/s. The profile of the blade was chosen as type Go 480 with a radius of 450 mm, and the weight of each blade was 91.72 N. The water flow on the spoon causes a blade reaction force of 11,996 N for centrifugal force and 1073 N for axial force. The torque produced from this reaction force is 775 Nm. The next plan is to calculate the force on the blade by calculating the moment of inertia, standard voltage, tensile stress, and shear stress. From the results of this strength calculation, the type of material that will be used in making the spoon can then be determined to ensure that the spoon is in a safe state during its operation but still efficient. Next is the process of making spoons, where the steps start from making patterns, making molds, smelting, and pouring the selected metal materials into the machining process.